Integration of graphene sensor with electrochromic device on modulus-gradient polymer for instantaneous strain visualization. (24th July 2017) - Yang, Tingting; Zhong, Yujia; Tao, Dashuai; Li, Xinming; Zang, Xiaobei; Lin, Shuyuan; Jiang, Xin; Li, Zhihong; Zhu, Hongwei
Abstract: In nature, some animals change their deceptive coloration for camouflage, temperature preservation or communication. This astonishing function has inspired scientists to replicate the color changing abilities of animals with artificial skin. Recently, some studies have focused on the smart materials and devices with reversible color changing or light-emitting properties for instantaneous strain visualization. However, most of these works only show eye-detectable appearance change when subjected to large mechanical deformation (100%–500% strain), and conspicuous color change at small strain remains rarely explored. In the present study, we developed a user-interactive electronic skin with human-readable optical output by assembling a highly sensitive resistive strain sensor with a stretchable organic electrochromic device (ECD) together. We explored the substrate effect on the electromechanical behavior of graphene and designed a strategy of modulus-gradient structure to employ graphene as both the highly sensitive strain sensing element and the insensitive stretchable electrode of the ECD layer. Subtle strain (0–10%) was enough to evoke an obvious color change, and the RGB value of the color quantified the magnitude of the applied strain. Such high sensitivity to smaller strains (0–10%) with color changing capability will potentially enhance the function of wearable devices, robots and prosthetics in the future.